Dose matrix conversion in terms of biological effective dose and equivalent dose in 2 Gy fractions (Revista de Física Médica, 2021)
Re-irradiation treatments are complex. Nowadays treatment  planning systems have developed tools that allow image registration and add different dose plans on registered images.  However, hypofractioned and accelerated treatments remain a challenge as evaluation of summed doses from different  fractioning are difficult to understand. On this basis, treatment  volume definition and dose prescription are sometimes limited  and unclear. A tool has been developed to convert absorbed  dose to Biologically Effective Dose and 2 Gy fractions equivalent  dose. This tool creates a standard DICOM dose file  that is possible to import on to the treatment planning system  and allows the evaluation of summed dose plans with different  fractioning. This works describes the tool creation and analyzes  its clinical use. Results show a correct alignment between  calculated dose matrices and the image set. It also shows  limitations on the evaluation of point doses, especially in the  boundaries of defined structures. Although this tool might be  useful in a clinical environment an understanding of its  limitations is required.
Keywords: BED; EQD2; radiobiology; re-irradiation; dosimetry